(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2013)
The development of controllers tuning equations PI, PID based on performance criteria is a methodology widely used in recent years. There numerous scientific publications where equations are reported of tuning used to tune controllers function of a particular process, and desired response in the control loop. In this article presents the development of a tuning equations for PID controllers based on the formulation of a new comprehensive performance criterion called FAD ®, which aims error minimizing deviation above or below the Set Point to regulatory control, depending on the restrictions of a specific process that can be approximated through a model represented by a transfer function FOPDT.